2011
DOI: 10.1007/s00011-011-0319-4
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory pattern recognition receptors and their ligands: factors contributing to the pathogenesis of preeclampsia

Abstract: This review summarizes recent advances in TLR- and RAGE-mediated signaling and the target molecules, and provides new insights into the pathogenesis of preeclampsia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 83 publications
1
25
0
Order By: Relevance
“…13) As expected from previously reported serum concentrations, 15) our current study strongly suggests that hypoxia and reoxygenation in the preeclamptic placenta contributes to systemic release of the danger signal HMGB1. Cellular debris (microparticles) from syncytiotrophoblasts is regarded as a possible mediator of the systemic inflammation that connects placentation failure in the first trimester to later onset of preeclampsia; HMGB1 and S100 family members are considered candidate functional surface antigen molecules on the microparticles.…”
Section: )supporting
confidence: 87%
See 1 more Smart Citation
“…13) As expected from previously reported serum concentrations, 15) our current study strongly suggests that hypoxia and reoxygenation in the preeclamptic placenta contributes to systemic release of the danger signal HMGB1. Cellular debris (microparticles) from syncytiotrophoblasts is regarded as a possible mediator of the systemic inflammation that connects placentation failure in the first trimester to later onset of preeclampsia; HMGB1 and S100 family members are considered candidate functional surface antigen molecules on the microparticles.…”
Section: )supporting
confidence: 87%
“…11,12) After reviewing the literature, we hypothesized that the inflammatory response induced in normal pregnancy, preeclampsia, and preterm birth may be regulated by changes in RAGE ligands. 13,14) We subsequently reported increased serum levels of two soluble RAGE ligands in preeclampsia patients, high-mobility group box 1 (HMGB1) and S100/calgranulin family member S100A12 (also known as extracellular newly identified RAGE-binding protein). 15) HMGB1 expression has also been reported in human term placenta.…”
Section: Introductionmentioning
confidence: 99%
“…Higher methylation was also observed in some genes in the preeclampsia (Jia et al 2012). Here, we showed that the differentially expressed genes in preeclampsia placental tissues were mainly enriched in several pathways associated with pregnancy maintenance, metabolism, oxidative stress and oxidative metabolism, cell cycle regulation, embryogenesis and development, implantation, placentation and decidualization, immune modulation, and vascular function (Zhou et al 2006;Laivuori 2007;Founds et al 2009;Johansson et al 2011;Løset et al 2011;Rajakumar et al 2011;Sado et al 2011;Tsai et al 2011;Jia et al 2012;Lapaire et al 2012). We summarized the major functional categories on the differential gene expression profile between preeclampsia and normal placentas ( Table 1).…”
Section: Preeclampsia Susceptibility Genesmentioning
confidence: 83%
“…This review provides a detailed overview of typical genome-wide studies that have been conducted so far on preeclamptic placental tissue samples (Zhou et al 2006;Laivuori 2007;Founds et al 2009;Johansson et al 2011;Løset et al 2011;Rajakumar et al 2011;Sado et al 2011;Tsai et al 2011;Jia et al 2012;Lapaire et al 2012).…”
Section: Review Of the Literaturementioning
confidence: 99%
“…Pathways related to stress, inflammation (including TLR signalling pathways), growth, tissue remodelling, and metabolism are all altered during preeclampsia (Sado, Naruse et al 2011). The differences might reflect acute inflammation secondary to microbial infection versus chronic inflammation secondary to oxidative stress.…”
Section: Prrs and Adverse Pregnancy Outcomesmentioning
confidence: 99%